Gestão democrática escolar: uma experiência em duas escolas públicas na rede municipal de João Pessoa-Paraíba - Silva, Kátia Valéria Ataíde e (2018)
This study deals with the construction of democratic management in the public school. The objective of the research was to analyze how the process of democratic management is given in two schools, in the municipal public network of João Pessoa, in Paraíba. To substantiate this study, reflections were taken on the democratic theoretical conceptions and management models built over historical time. A contextualization was carried out on the management reform of the Brazilian state and its influence in the field of educational policy, placing the policy of democratization of the administration in the years 1990. On Democratic management, the historical, legal, principles and collegiate instances have been addressed. Democratic management is a social practice, characterized by the engagement and participation of the school community – parents, students, employees, teachers, specialists, managers – in acting autonomous and dialogic. The research is inserted into the qualitative approach, taking into account the categories based on the dialectical method. For the collection of data was carried out the documentary and bibliographic research, interviews with 28 subjects of two public schools, our empirical field. The temporal resection of the research is located in the period from 2015 to 2017. The data resulting from the interviews were analyzed by the content analysis technique, systematized by Bardin (2010). The research showed that the majority of respondents, in the two schools investigated, have an understanding of democratic management, emphasizing the mechanisms of participationdirect elections for manager, school board, class council, pedagogical political project, pedagogical planning and student Assembly-and collective work, as elements of significance in the school organization. In spite of the living existence of mechanisms of participation, there were evidences of compromising elements of the process of construction of the Democratic school management, the example of the school board, which, although it constitutes a representative instance, there are problems in the process of choice of representatives; The pedagogical planning, valued and participatory, does not involve the whole community, because it limits the process of discussions and referrals, to managers, teachers and specialists. The class council is carried out, excluding students. These elements begin to require a careful formative process of discussion about democratic management and its developments. Finally, the study points out that there are changes in the research schools: improvement of the interpersonal school relationship; Integration, dialogue between school and community; Decreased evasion; Improvement in the quality of education. The strengthening of partnerships of the school with institutions and the recognition of the community for the work committed and welcoming in the two schools, are other changes identified.